Hubungan Kadar D-dimer dengan Penyakit Cerebrovascular pada Pasien Covid-19 - Ayyas Robbani; Santun Bhekti Rahimah; Usep Abdullah Husin (UNISBA Press, 2024)
Abstract. D-dimer is a potential screening tool for venous thromboembolism (VTE) in Coronavirus disease-19 (COVID-19) patients, and is based on D-dimer elevation. In severe cases of COVID-19, hypercoagulability can occur which causes thrombus formation, then results in blockage of blood vessels. When a blockage occurs in the brain, it can cause cerebrovascular disease. Cerebrovascular disease is one of the most common causes of COVID-19. This study aims to determine the relationship between increased D-dimer levels in COVID-19 patients with the incidence of Cerebrovascular disease. The study design used a cross sectional design, data obtained in the medical records of inpatients for the 2021-2022 period of the Al-Ihsan Regional General Hospital (RSUD) Bandung Regency. The sampling technique uses a total sampling of 188 samples that have met the inclusion and exclusion criteria. Research method of the relationship of D-dimer levels with the incidence of Cerebrovascular disease using the chi-square test. From the results of the study, it was found that COVID-19 patients at Al-Ihsan Hospital who experienced increased levels of D-dimer (≥500 ng / ml) as many as 152 patients (80.9%) and patients with cerebrovascular disease as many as 34 patients (18.1%). Based on the chi-square test, it can be concluded that there is no relationship between D-dimer levels and the incidence of cerebrovascular disease at Al-Ihsan Hospital, Bandung Regency for the 2021-2022 period. Elevated D-dimer levels in COVID-19 patients are not associated with cerebrovascular disease. Abstrak. D-dimer adalah alat skrining potensial untuk venous thromboembolism (VTE) pada pasien Coronavirus disease-19 (COVID-19), dan berdasarkan elevasi D-dimer. Pada kasus COVID-19 yang parah dapat terjadi hiperkoagulabilitas yang menyebabkan pembentukan thrombus, kemudian mengakibatkan penyumbatan pada pembuluh darah. Apabila penyumbatan terjadi di otak, dapat menyebabkan penyakit cerebrovascular. Penyakit Cerebrovascular merupakan salah satu penyebab paling umum COVID-19. Penelitian ini bertujuan untuk mengetahui hubungan peningkatan kadar D-dimer pada pasien COVID-19 dengan kejadian penyakit Cerebrovascular. Rancangan penelitian menggunakan desain cross sectional, data diperoleh dalam rekam medik pasien rawat inap periode 2021-2022 Rumah Sakit Umum Daerah (RSUD) Al-Ihsan Kabupaten Bandung. Teknik pengambilan sampel menggunakan total sampling dengan jumlah sampel sebanyak 188 yang telah memenuhi kriteria inklusi dan eksklusi. Metode penelitian hubungan kadar D-dimer dengan kejadian penyakit Cerebrovascular menggunakan uji chi-square. Dari hasil penelitian diperoleh bahwa pasien COVID-19 di RSUD Al-Ihsan yang mengalami peningkatan kadar D-dimer (≥500 ng/ml) sebanyak 152 pasien (80,9%) dan pasien yang terjadi penyakit cerebrovascular sebanyak 34 pasien (18,1%). Berdasarkan uji chi-square dapat disimpulkan bahwa tidak terdapat hubungan antara kadar D-dimer dengan kejadian penyakit cerebrovascular di RSUD Al-Ihsan Kabupaten Bandung periode 2021-2022. Peningkatan kadar D-dimer pada pasien COVID-19 tidak berkaitan dengan penyakit cerebrovascular.